2019
DOI: 10.1142/s2424835519500176
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Primary Repair in Professional Athletes with Chronic Radial Collateral Ligament Injuries of Thumb Metacarpophalangeal Joint

Abstract: Background: Management of grade III injuries of the radial collateral ligament (RCL) of the thumb is controversial. These injuries are often treated with early surgery. However, early surgery may not be practical for the professional athlete. We report on the outcome of delayed primary repair of chronic RCL injuries without the use of tendon grafts or tendon transfers. Methods: Twelve elite professional athletes with 15 soft tissue RCL injuries who underwent delayed surgery (greater than 6 weeks) were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Several authors have reported equivalent outcomes after surgical repair despite delayed treatment. 4,15,16 A systematic review of six studies reported excellent results in 80% of patients after autograft reconstruction, who were able to return to work with minimal disability. 9 Others have reported worsened outcomes in this setting, including decreased grip strength and persistent disability on postoperative disabilities of the arm, shoulder and hand (DASH) scores.…”
Section: Collateral Ligament Injuriesmentioning
confidence: 99%
“…Several authors have reported equivalent outcomes after surgical repair despite delayed treatment. 4,15,16 A systematic review of six studies reported excellent results in 80% of patients after autograft reconstruction, who were able to return to work with minimal disability. 9 Others have reported worsened outcomes in this setting, including decreased grip strength and persistent disability on postoperative disabilities of the arm, shoulder and hand (DASH) scores.…”
Section: Collateral Ligament Injuriesmentioning
confidence: 99%
“…[58][59][60][61] Thumb ulnar collateral ligament injuries are very common, and are often seen in skiing, basketball, and football athletes. [62][63][64]…”
Section: Hand/wristmentioning
confidence: 99%
“…Acute hook of the hamate fractures can occur in golfers and baseball players; in the former, when striking the ground during the swing, and in the latter while checking a swing 58–61. Thumb ulnar collateral ligament injuries are very common, and are often seen in skiing, basketball, and football athletes 62–64…”
Section: Upper-extremity Injuriesmentioning
confidence: 99%